Ergonomic Risk Levels in Administrative Computer Work Using REBA and ROSA: Tingkat Risiko Ergonomis dalam Pekerjaan Komputer Administratif Menggunakan REBA dan ROSA - Andi Priyo Utomo; Boy Isma Putra (Academia Open, 2025)
General Background: Musculoskeletal disorders are cumulative injuries in the musculoskeletal system commonly associated with prolonged non-ergonomic occupational activities, particularly in office environments. Specific Background: Administrative employees frequently perform tasks involving continuous computer usage for approximately seven hours daily, which may result in discomfort and postural strain. Knowledge Gap: Limited workplace-based assessments simultaneously examine overall body posture and office workstation conditions among administrative personnel in agricultural equipment companies. Aims: This study aims to evaluate administrative employee posture and workstation conditions at PT. XYZ through Rapid Entire Body Assessment and Rapid Office Strain Assessment supported by Nordic Body Map data. Results: Data from 15 respondents indicated predominant complaints in the waist, right elbow, and neck regions. The posture evaluation produced a score of 5, indicating a medium level requiring corrective action, while workstation evaluation also generated a score of 5, demonstrating a high level requiring immediate modification. Identified issues included non-adjustable chairs, suboptimal arm support, low monitor position, and prolonged task duration. Recommended interventions comprised periodic muscle stretching after two hours of screen activity, replacement of seating facilities with adjustable ergonomic chairs, establishment of standard operating procedures for external mouse utilization, and additional document storage facilities. Novelty: This study integrates multi-instrument ergonomic assessment to generate targeted intervention recommendations within an administrative office setting. Implications: The findings provide evidence-based ergonomic guidance for reducing musculoskeletal complaints and improving workplace comfort among office personnel. Highlights: Postural Evaluation Demonstrated Moderate Musculoskeletal Hazard Requiring Corrective Action Soon. Workplace Facility Assessment Revealed Urgent Modification Needs Related to Seating and Monitor Placement. Reported Discomfort Was Most Frequent in Waist, Elbow, and Cervical Regions. Keywords: Musculoskeletal Disorders, Nordic Body Map, Rapid Entire Body Assessment, Rapid Office Strain Assessment, Office Ergonomics